Customer Satisfaction and Service Quality : A Case Study of Bank Islam Malaysia Berhad (BIMB) - Fozi, Awang (2009)
The operation of Islamic bank derives from the Islamic Law and thus differs in spirit, cultural background and practice from conventional bank operations. In view of the strong competition, customer expectation to receive high quality services, and quick changes of technology, Islamic banks must therefore think strategically by providing high quality products and services to satisfy their customers. The objectives of this study to measure customer satisfaction by using service quality dimensions; compliance , assurance, reliability, tangible, empathy and responsiveness (CARTER). A survey of 177 customers at three BIMB branches located in Northern Kedah was conducted. The data generated through the survey was analysed and a regression analysis was also carried out between the six dimensions and customer satisfaction. The result showed that the customers are satisfied with the products and services offered by the BIMB. The linear regression results indicate that there was a positive and statistically significant relationship between overall customer satisfaction and the SERVQUAL dimensions at the BIMB. The study also showed that the five dimensions; compliance, assurance, reliability, empathy and responsiveness are statistically significant predictors of customer satisfaction. Among the five dimensions responsiveness and reliability having the greatest overall impact.